Analisis Yuridis Amar Putusan Dalam Perkara Citizen Lawsuit (CLS) Terkait Ijazah Jokowi: Studi Kasus Putusan Nomor 211/Pdt.G/2025/PN Skt - Agnesia Winda Sari; Dhiva Anggun Insani; Dita Permata Sari; Kasih Fitria Hastuti; Pradinda Puspa Rinjani; Endang Yuliana Susilowati (Majelis: Jurnal Hukum Indonesia, 2026)
Citizen Lawsuit (CLS) is a legal instrument through which citizens file lawsuits against the government for its negligence in fulfilling and protecting public rights. This study aims to analyze juridically the ruling in the CLS case concerning Jokowi’s diploma based on Decision Number 211/Pdt.G/2025/PN Skt. The method employed is normative legal research using both the statute approach and the case approach. Primary legal materials consist of court decisions, while secondary legal materials include relevant literature, journals, and legal doctrines. The findings indicate that the judges’ considerations in this case focused on the plaintiff’s legal standing and the government’s responsibility to fulfill citizens’ rights. The judges appear to have adopted a more progressive perspective in assessing state responsibility, although the implementation of the ruling still faces obstacles due to difficulties in effective enforcement. This study emphasizes the strategic role of CLS as a mechanism for monitoring public policy while also highlighting the urgency of strengthening regulations and ensuring consistency in judicial decisions to provide optimal protection of citizens’ rights.